2018
DOI: 10.3727/105221617x15124844266408
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Exercise on Fatty Liver Disease

Abstract: The increasing prevalence of obesity has made nonalcoholic fatty liver disease (NAFLD) the most common chronic liver disease. As a consequence, NAFLD and especially its inflammatory form nonalcoholic steatohepatitis (NASH) are the fastest increasing etiology of end-stage liver disease and hepatocellular carcinoma. Physical inactivity is related to the severity of fatty liver disease irrespective of body weight, supporting the hypothesis that increasing physical activity through exercise can improve fatty liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
156
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(183 citation statements)
references
References 113 publications
8
156
1
3
Order By: Relevance
“…(1,3) Currently, no effective drugs are available for the treatment of NAFLD and NASH, and only lifestyle changes and weight control can be recommended. (26) Here, we showed that Card6 down-regulation was associated with fatty livers and that Card6 negatively regulated insulin resistance, hepatic steatosis, and the inflammatory response in both dietary and genetic NAFLD. Card6 inhibited p38 and Jnk signaling by suppressing the activation of their upstream kinase Ask1.…”
Section: Discussionmentioning
confidence: 76%
“…(1,3) Currently, no effective drugs are available for the treatment of NAFLD and NASH, and only lifestyle changes and weight control can be recommended. (26) Here, we showed that Card6 down-regulation was associated with fatty livers and that Card6 negatively regulated insulin resistance, hepatic steatosis, and the inflammatory response in both dietary and genetic NAFLD. Card6 inhibited p38 and Jnk signaling by suppressing the activation of their upstream kinase Ask1.…”
Section: Discussionmentioning
confidence: 76%
“…However, these studies observed the high measure of maximal oxygen uptake (VO 2peak ) in mild NAFLD, confirming the vital function of exercise training in the management of this type of patients [12]. Also, other studies provided that physical exercise and dietary control reduce steatosis [13][14][15], liver fat content [16][17][18], depression status [19,20], ventilatory marker dysfunctions [21], and slow down progression of T2DM [22].…”
Section: Introductionmentioning
confidence: 69%
“…Sufficient doses of physical exercise could also have a major impact in reducing the adverse metabolic effects of unfavorable lifestyle. Regular physical activity may also be expected to lead to significant long-term health benefits in reducing hepatic steatosis and insulin resistance [35,45,[48][49][50]. In accordance with this view, moderate or vigorous physical activity were recently shown to reduce fat, inflammation and oxidative stress in the liver even in cases without any notable changes in BMI status [35].…”
Section: Discussionmentioning
confidence: 90%